Sistem Kontrol Dan Monitoring Kualitas Ph Air Pada Ground Tank Berbasis Mikrokontroller Di Bandar Udara Tjilikriwut Palangkaraya - Iswahyudi, Prasetyo; Maulana Anifa Silvia (Prodi Teknik Elektro Universitas PGRI Banyuwangi, 2024)
Abstract – The centralized water pH quality monitoring control system uses a microcontroller as the control center and program. By using theoretical basics regarding relays, microcontrollers and other electronic components, the author designed a centralized monitoring control system using a computer HMI (Human Machine Interface) as a display with a pH sensor for each water quality situation. The pH sensor is an analog data reader, where the reading results will be processed by the microcontroller which will then activate the relays so that the acid-base solution pump is active when the water pH is unstable. Keywords — Monitoring controls, Microcontrollers, pH Sensors